Benchmarking the Objectives of Shariah in Practice: A Comparative Maqāṣid Index Analysis of Five Leading Islamic Banks Across OIC Countries - Nashruddin, Ahmad (SMART Insight, 2024)
This study examines the extent to which leading Islamic banks operationalize the higher objectives of Islamic law (Maqāṣid al-Sharīʿah) in contemporary banking practice. Moving beyond conventional financial performance indicators, the research develops and applies a comprehensive six-dimensional Maqasid Index (MI-6D). Using a deductive, comparative research design, the study analyzes 2024 Integrated Annual Reports and Sustainability/ESG Reports of five systemically important Islamic banks across Organisation of Islamic Cooperation (OIC) countries: Bank Syariah Indonesia, Al Rajhi Bank (Saudi Arabia), Maybank Islamic (Malaysia), Meezan Bank (Pakistan), and Kuveyt Türk Participation Bank (Türkiye). Employing qualitative content analysis and proxy-based indicators derived from established Maqasid literature and ESG frameworks, the findings reveal significant variation in the practical realization of Maqasid objectives across regions. While all sampled banks demonstrate strong compliance in Shariah governance and wealth preservation, notable differences emerge in social development, environmental stewardship, and real-sector engagement. Banks operating in jurisdictions with mature sustainability frameworks exhibit more comprehensive disclosure and stronger alignment with the expanded Maqasid paradigm, particularly in ḥifẓ al-biʾah. The study contributes theoretically by operationalizing a contemporary six-dimensional Maqasid Index and empirically by providing an up-to-date cross-country benchmark.